Asparagine and dough quality: Gluten strength factors in hard red spring wheat. Issue 1 (19th December 2022) - Trevisan, Susane; Khorshidi, Ali Salimi; Sopiwnyk, Elaine; Xie, Yi; Zhou, Zhaoxian; House, James D.; Scanlon, Martin G.
Abstract: Background and Objectives: Safety aspects regarding free asparagine concentration in wheat arise because of its acrylamide formation potential in baked wheat products. Free asparagine concentration in wheat is affected by environment, genotype, and nitrogen and sulfur fertilization, which also affect wheat protein content and composition. Changing protein content and composition affects gluten strength, altering product quality. This study investigated how gluten strength was affected by environment, genotype, and fertilization treatments grown under commercially relevant conditions. Findings: Environment predominated in affecting dough extensibility and genotype primarily affected resistance to extension, with minimal effects from fertilization treatments. Differences in extensigraph parameters at two resting times segregated genotypes according to gluten strength. Conclusions: Factors affecting free asparagine accumulation in wheat also affect gluten strength. Genotype and environment require primary attention since they play an important role in both wheat safety and quality. Significance and Novelty: The lack of studies investigating the impact of factors affecting free asparagine concentration on the gluten strength of wheat has implications for the global wheat market. From a novel perspective on dough extensibility and resistance to extension, the effects of environment, genotype, and fertilization on the gluten strength of commercially important wheat varieties are considered in a food safety context.